2020
DOI: 10.7554/elife.60031
|View full text |Cite
|
Sign up to set email alerts
|

The SSVEP tracks attention, not consciousness, during perceptual filling-in

Abstract: Research on the neural basis of conscious perception has almost exclusively shown that becoming aware of a stimulus leads to increased neural responses. By designing a novel form of perceptual filling-in (PFI) overlaid with a dynamic texture display, we frequency-tagged multiple disappearing targets as well as their surroundings. We show that in a PFI paradigm, the disappearance of a stimulus and subjective invisibility is associated with increases in neural activity, as measured with steady-state visually evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 165 publications
1
11
0
Order By: Relevance
“…A careful examination of these two theories leads to the conclusion that the NC of AC and PC coincide and in fact, the two consciences are mirror images of each other; they are two faces of the same coin, that is, of the only consciousness, in which cognitive and subjective contents are simultaneously Frontiers in Psychology | www.frontiersin.org present. New findings from recent studies on attention (Davidson et al, 2020) and consciousness (Mashour et al, 2020) are converging to validate the hypotheses set out in this article. We hope this trend continues.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A careful examination of these two theories leads to the conclusion that the NC of AC and PC coincide and in fact, the two consciences are mirror images of each other; they are two faces of the same coin, that is, of the only consciousness, in which cognitive and subjective contents are simultaneously Frontiers in Psychology | www.frontiersin.org present. New findings from recent studies on attention (Davidson et al, 2020) and consciousness (Mashour et al, 2020) are converging to validate the hypotheses set out in this article. We hope this trend continues.…”
Section: Discussionsupporting
confidence: 64%
“…In the current state of the field, the consensus is increasing in favor of the hypothesis that there is a clear separation between attention and consciousness ( van Boxtel et al, 2010 ; Cohen et al, 2012 ; Koch and Tsuchiya, 2015 ; Baier et al, 2020 ; Davidson et al, 2020 ). In this context, attention is believed to select from among the unconscious perceptual images coming from either the environment or memory, those that are then made conscious by the neural correlates of consciousness (NCC; Mashour et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, higher harmonic responses are not even reported (e.g., Bekhtereva, Pritschmann, Keil, & Müller, 2018;Min, Dähne, Ahn, Noh, & Müller, 2016;Paulk, Kirszenblat, Zhou, & van Swinderen, 2015;Coia, Jones, Duncan, & Crognale, 2014;Kuś et al, 2013;Cottereau et al, 2011;Wattam-Bell et al, 2010;Di Russo et al, 2007;Müller et al, 2006;Braddick, Birtles, Wattam-Bell, & Atkinson, 2005;Chen, Seth, Gally, & Edelman, 2003;Heinrich & Bach, 2001;Regan & Regan, 1988a;Tononi et al, 1998;Peterzell & Norcia, 1997;Müller, Teder, & Hillyard, 1997;Morgan, Hansen, & Hillyard, 1996, or are extirpated by narrow [band-pass, Gabor, etc. ] filtering, e.g., Davidson, Mithen, Hogendoorn, van Boxtel, & Tsuchiya, 2020;Miskociv & Keil, 2013;Anderson & Müller, 2010;Regan, 1975). Does it matter?…”
Section: Higher Harmonicsmentioning
confidence: 99%
“…the RSVP response) contaminating our measure of alpha band activity within the preparatory window, we avoided the use of a sliding window spectrogram (e.g. (Davidson et al, 2020)), or time-frequency decomposition via wavelet transform (e.g. (Benwell et al, 2017; Iemi et al, 2017)).…”
Section: Methodsmentioning
confidence: 99%